HUBUNGAN TOXIC PARENTING DENGAN SELF ESTEEM SISWA DI SMA KRISTEN - Saiputa, Anaci Omega; Wijaya, R. Pasifikus Christa; Artati, Mardiana; Marni, Marni (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Toxic parenting is a detrimental parenting pattern that can hinder adolescents’ psychological development, particularly in shaping their self-esteem. This parenting style includes excessive demands, emotional neglect, and demeaning criticism directed toward the child. This study aims to examine the relationship between toxic parenting and self esteem among students at SMA Kristen 1 Kalabahi. Employing a quantitative approach with a correlational design, the study involved 215 students aged 14-19 years selected using a quota sampling technique. The instruments used were the Toxic Parenting Scale based on the aspects proposed by Dunham, Dermer, and Carlson and the Self-Esteem Inventory developed by Coopersmith. The results indicated a significant negative relationship between toxic parenting and self-esteem (r = -0.306; p = 0.000), meaning that higher levels of toxic parenting are associated with lower levels of self-esteem. Most students were categorized as having moderate self-esteem (82.8%) and moderate levels of toxic parenting (76.3%). Regression analysis showed that toxic parenting contributed 9.36% to the variance in self-esteem, with the dismissive parents aspect being the most dominant factor in lowering students’ self-esteem. These findings highlight the crucial role of emotional bonding between parents and children in fostering healthy self-esteem, and suggest the need for parenting education interventions to promote healthier parenting practices that support adolescents’ psychological development.. ABSTRAK Toxic parenting merupakan pola asuh yang merugikan dan dapat menghambat perkembangan psikologis remaja, terutama dalam pembentukan self esteem. Pola asuh ini mencakup perilaku orang tua yang menuntut secara berlebihan, kurang memberi dukungan emosional, serta cenderung meremehkan atau mengkritik anak. Penelitian ini bertujuan untuk mengetahui hubungan antara toxic parenting dengan self esteem pada siswa di SMA Kristen 1 Kalabahi. Penelitian menggunakan metode kuantitatif dengan desain korelasional, melibatkan 215 siswa berusia 14–19 tahun yang dipilih melalui teknik quota sampling. Instrumen penelitian terdiri dari Skala Toxic Parenting berdasarkan aspek Dunham, Dermer, & Carlson serta Self Esteem Inventory dari Coopersmith. Hasil penelitian menunjukkan adanya hubungan negatif yang signifikan antara toxic parenting dan self esteem (r = -0,306; p = 0,000), yang berarti semakin tinggi tingkat toxic parenting yang dialami siswa maka semakin rendah self esteem mereka. Mayoritas siswa berada pada kategori self esteem sedang (82,8%) dan toxic parenting kategori sedang (76,3%). Analisis regresi menunjukkan bahwa toxic parenting memberikan kontribusi sebesar 9,36% terhadap variasi self esteem, dengan aspek dismissive parents menjadi faktor yang paling dominan dalam menurunkan self esteem siswa. Temuan ini menegaskan bahwa kualitas hubungan emosional antara orang tua dan anak sangat penting dalam membangun self esteem yang sehat, serta perlunya intervensi berbasis edukasi parenting untuk meningkatkan pola asuh positif dalam mendukung perkembangan psikologis remaja..